Comparative techno-economic and environmental analysis of a new CO2 to diethyl carbonate production process. (20th February 2023) - Nguyen, Thuy T.H.; Putro, Wahyu S.; Hamura, Satoshi; Nakashige, Makoto; Choi, Jun-Chul; Fukaya, Norihisa; Taniguchi, Satoshi; Yamaki, Takehiro; Hara, Nobuo; Kataoka, Sho
Abstract: Direct conversion of CO2 to dialkyl carbonates such as diethyl carbonate (DEC) can contribute to mitigate CO2 emissions. We previously proposed a new DEC synthesis method from the reaction of CO2 and tetraethoxysilane (TEOS), an expensive functional chemical. After being used for DEC synthesis, TEOS can be regenerated from reaction of ethanol and hexaethoxy disiloxane (DS), the byproduct produced along with DEC. However, TEOS regeneration requires several processing units and high energy demand. In this study, we designed and evaluated feasibility of this new DEC synthesis process. Based on data obtained from lab experiments, the entire process, which comprised DEC synthesis and TEOS regeneration sections, was designed and optimized using process simulator Pro/II. Cradle-to-gate life cycle assessment method was applied to comprehensively evaluate the total CO2 emissions caused by the consumption of raw materials and utilities in DEC synthesis and TEOS regeneration sections. In addition, the total production cost was evaluated. On the basis of the evaluation results, process hotspots were identified. Optimal conditions used for TEOS regeneration (ethanol/DS = 18.2) were proposed to improve total process performances. The total production cost and CO2 emissions are 1.7 $/kg DEC, 3.6 kg CO2 /kg DEC, respectively. The new process was compared to the most commonly used process which synthesizes DEC from the reaction of CO2 with ethanol, assisted by the dehydrating agent 2-cyanopyridine. Our results show that the new DEC synthesis process gains higher economic and environmental viability. Highlights: A new process synthesizing DEC from CO2 and TEOS was rigorously designed. Economic viability and potential CO2 emissions reduction were evaluated. Regeneration of TEOS was the key to enhancing total process feasibility. Optimal regeneration condition was found to reduce both cost and CO2 emissions. The new process can be a competitive alternative for DEC synthesis.